Novel derivatives of substituted 6-fluorobenzothiazole diamides: synthesis, antifungal activity and cytotoxicity - Pejchalová, Marcela; Havelek, Radim; Královec, Karel; Růžičková, Zdeňka; Pejchal, Vladimír (Springer, 2017)
A new series of 1-[(1R)-1-(6-fluoro-1,3-benzothiazol-2-yl) ethyl]-3-substituted phenyl diamides were synthesized in vitro as potential antifungal agents. Chemical structures of the synthesised compounds were substantiated by IR, H-1, C-13, F-19 nuclear magnetic resonance spectra, high resolution mass spectrometry, elemental analysis and also by X-ray diffraction. In addition, the cytotoxicity of the most active compounds was investigated against cancer cell line (Jurkat) and one type of normal lung fibroblast cells (MRC-5) by (2,3-bis-(2-methoxy4-nitro-5-sulfophenyl)-2H-tetrazolium-5-carboxanilide) tetrazolium salt reduction assay, propidium iodide flow cytometry assay and xCELLigence system allowing a label-free assessment of the cells proliferation. Compounds indicated as 11e, 11g, 11j, 11n and 11o, were the best of the series, showing minimum inhibitory concentration values of 6.25-50 mu g/mL against pathogenic strains Candida albicans HE 169, Candida tropicalis 31/HK and Candida parapsilosis p69. Moreover compounds 11e, 11g, 11j and 11o did not show any cytotoxic effect against human Jurkat and MRC-5 cells.
Nové deriváty substituovaných 6-fluorbenzthiazolových diamidů: syntéza, antifungální aktivita a cytotoxicita
Keywords: Benzothiazole derivatives; Diamide; Candida; Antifungal activity; Cytotoxicity; Benztiazolové deriváty; diamidy; Candida; antifungální aktivita; cytotoxicita